Pengaruh Uang Elektronik, Uang Kartal dan Tingkat Suku Bunga Terhadap Kecepatan Perputaran Uang di Indonesia - Muhammad Rizki; Khairul Amri; Rachmi Meutia (Sekretariat Pusat Lembaga Komunitas Informasi Teknologi Aceh, 2023)
This research was conducted to see the influence of electronic money, currency and interest rates on the velocity of money in Indonesia. The method used is Autoregressive Distributed Lag (ARDL). The data used is secondary data sourced from Bank Indonesia and the Central Statistics Agency from 2010-2021 in quarterly form. Electronic money, currency and interest rates are independent variables, while velocity of money is the dependent variable. The results of this research show that (1) Electronic Money variables in the long term are able to have a significant influence on the velocity of money in Indonesia, however, in the short term Electronic Money is not able to have an influence on the velocity of money in Indonesia. (2) Currency variables in the long term and short term are able to have a significant influence on the velocity of money in Indonesia. (3) Interest rate variables in the long term and short term are able to have a significant influence on the velocity of money in Indonesia. (4) Overall, the variables Electronic Money, Currency and Interest Rates are able to have a significant influence on the velocity of money in Indonesia.